Repurposing leflunomide for relapsed/refractory multiple myeloma: a phase 1 study. Issue 7 (6th June 2020) - Rosenzweig, Michael; Palmer, Joycelynne; Tsai, Ni-Chun; Synold, Tim; Wu, Xiwei; Tao, Shu; Hammond, Samantha N.; Buettner, Ralf; Duarte, Lupe; Htut, Myo; Karanes, Chatchada; Nathwani, Nitya; et al.
Abstract: The inexpensive, well-tolerated, immunomodulatory agent leflunomide, used extensively for the treatment of rheumatoid arthritis, has been shown to produce significant activity against multiple myeloma (MM) in pre-clinical studies. We conducted a phase 1 study (clinicaltrials.gov: NCT02509052) of single agent leflunomide in patients with relapsed/refractory MM (≥3 prior therapies). At dose levels 1 and 2 (20 and 40 mg), no dose-limiting toxicities (DLTs) were observed. At dose level 3 (60 mg), one patient experienced elevated alanine aminotransferase; an additional three patients were enrolled at this dose level without further DLTs. Overall, toxicities were infrequent and manageable. Nine out of 11 patients achieved stable disease (SD), two subjects experiencing SD for nearly one year or longer. The tolerable safety profile of leflunomide, combined with a potential disease stabilization, is motivating future studies of leflunomide, in combination with other MM drugs, or as an approach to delay progression of smoldering MM.